Św. Paraskiewa-Petka z Epiwatu – kilka uwag o serbizacji kultu - Gapska, Dominika (Fundacja "Oikonomos", 2019)
The text discusses the problem of serbianisation of the cult of St. Parascheva of the Balkans not yet analyzed in the studies on the saint. The discussion is based on older and newer liturgical texts (lives, liturgical poetry), showing the various stages of the process of incorporating the image of Parascheva into the framework of the Serbian model of spirituality
St. Parascheva of the Balkans – a few remarks on serbianisation of the cult
Keywords: St. Parascheva; Serbian female saints; Serbian hagiography; Serbian hymnography; Serbian literature; Serbian medieval literature